Digestibilidad in vivo de saccharina rústica con diferentes niveles de urea para la alimentación de cuyes (Cavia porcellus) - Nero Granda, Geovanna Fernanda (2017)
The objective of this research was to determine digestibility in vivo of rustic saccharin in guinea pigs, as effect of different levels of urea and assess its chemical composition. Three treatments were made with rustic saccharin 0.5, 1 and 1.5% of urea per treatment. Besides, a Latin square design was applied with three treatments, three repetitions in three different times. Also, male guinea pigs with an average weight of 800 to 900 grams were selected randomly, three animals in each treatment. The food supply was in the morning and the afternoon. The studied variables were: chemical composition of treatments (crude protein (CP), dry matter (DM), crude fiber, ether extract, free extract of nitrogen and ash), as well as, the in vivo digestibility, dry matter (DMS) and crude protein (DPC). The statistical analysis was performed using the statistical program SAS (SAS University Edition), in which the main effects were diets, the time and their interaction and the random effect is the animal selected to the ration. The most notable changes of the chemical composition were observed in the level of crude protein. The inclusion of a 1% urea in chopped sugar cane, caused an increase (P<0,001) of 6.51 percent saccharin protein level. Differences were not detected due to the inclusion of different levels of urea in the saccharin, on the digestibility of DM and PC (P>0,309), obtaining half to 67.4% digestibility for DM and 67.2% for the PC. Despite of differences in digestibility, averages were significant between treatments, a high standard error did not allow to detect statistical differences. The chemical composition of saccharin analyzed with different levels of urea reached range 6.29 to 11.2% crude protein, higher level of urea to a higher level of crude protein; however the increase of non-protein nitrogen does not guarantee a greater use of it in the body of the Guinea pig. Key words: dry matter, crude protein, urea, saccharin and digestibility.